2018
DOI: 10.1186/s13071-018-3079-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Taenia saginata taeniosis/cysticercosis: a systematic review of the distribution in the Americas

Abstract: BackgroundThe distribution of Taenia saginata in the Americas is unclear. Establishing the distribution, economic burden, and potentials for control of bovine cysticercosis is increasingly important due to the growing demand for beef. This paper aims to take the first step and reviews the recent distribution of T. saginata taeniosis and bovine cysticercosis on a national level within the Americas.MethodsWe undertook a systematic review of published and grey literature for information on the occurrence, prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 74 publications
1
22
0
1
Order By: Relevance
“…Overall, the reported prevalence estimates of taeniosis were in line with those reported in eastern and southern Africa [12] and in the Americas [13], but higher than those reported in western and eastern Europe [9, 10]. In contrast to certain areas in eastern and southern Africa where consumption of raw beef is a culinary habit [12], traditional dishes in West and Central Africa include mainly stews with typically extended cooking times [29, 30], thereby decreasing the risk of exposure to viable T. saginata cysts.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, the reported prevalence estimates of taeniosis were in line with those reported in eastern and southern Africa [12] and in the Americas [13], but higher than those reported in western and eastern Europe [9, 10]. In contrast to certain areas in eastern and southern Africa where consumption of raw beef is a culinary habit [12], traditional dishes in West and Central Africa include mainly stews with typically extended cooking times [29, 30], thereby decreasing the risk of exposure to viable T. saginata cysts.…”
Section: Discussionsupporting
confidence: 82%
“…We generally found prevalences in both cattle and humans to be higher than that reported in western Europe [20] comparable with eastern Europe [21], South America [22] and the Middle East [12] but lower than in Africa [23]. This may be related to standards of sanitation and veterinary supervision of the slaughter of livestock.…”
Section: Discussionmentioning
confidence: 57%
“…However, comparison between studies is challenging due to their variability in design (variable factors including, for example, duration of study, inclusion of only certain target/age groups, different diagnostic methods used, randomization of participants, geographical coverage). The adoption of a consensus protocol for taeniosis surveillance purposes by clinical investigators such that bias is minimized is therefore highly recommended, as previously suggested [ 40 ].…”
Section: Discussionmentioning
confidence: 99%